Molecular cloning, expression profiles, and characterization of a novel polyphenol oxidase (PPO) gene in Hevea brasiliensis. Issue 10 (3rd October 2014) - Li, Dejun; Deng, Zhi; Liu, Changren; Zhao, Manman; Guo, Huina; Xia, Zhihui; Liu, Hui
Abstract: The polyphenol oxidase (PPO) is involved in undesirable browning in many plant foods. Although the PPOs have been studied by several researchers, the isolation and expression profiles of PPO gene were not reported in rubber tree. In this study, a new PPO gene, HbPPO, was isolated from Hevea brasiliensis . The sequence alignment showed that HbPPO indicated high identities to plant PPOs and belonged to dicot branch. The cis -acting regulatory elements related to stress/hormone responses were predicted in the promoter region of HbPPO . Real-time RT-PCR analyses showed that HbPPO expression varied widely depending on different tissues and developmental stages of leaves. Besides being associated with tapping panel dryness, the HbPPO transcripts were regulated by ethrel, wounding, H2 O2, and methyl jasmonate treatments. Moreover, the correlation between latex coagulation rate and PPO activity was further confirmed in this study. Our results lay the foundation for further analyzing the function of HbPPO in rubber tree. Graphical abstract: : The WRKY71OS and transcription initiation site were highlighted with square frame and bold letter, respectively. The other cis -acting regulatory elements were underlined.